2019
DOI: 10.22207/jpam.13.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Infection Control Practices to Manage Hospital Acquired Infections

Abstract: Hospital-acquired infections affect millions of patients worldwide each year and result in massive preventable healthcare costs. Many of the organisms that cause these infections survive on routine healthcare equipment and are easily transmitted from patient to patient when healthcare professionals and facilities do not comply with infection prevention and control practices. They are particularly dangerous for high-risk patients and patients in intensive care units. Hence the present study involved the impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[ 23 ], in the present study, a decrease in the rate of SSI was observed, which is consistent with a study conducted by Jayasree and Afzal in 2019. According to Jayasree and Afzal's study, adherence to the infection control guideline reduced the rate of SSI [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ], in the present study, a decrease in the rate of SSI was observed, which is consistent with a study conducted by Jayasree and Afzal in 2019. According to Jayasree and Afzal's study, adherence to the infection control guideline reduced the rate of SSI [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is an established fact that strict compliance to aseptic precautions during catheterisation and central line insertion reduce UTIs and CLABSIs, while adherence to infection control guidelines reduce SSI rates. [ 19 20 ] As per a study in a hospital setting in Taiwan and New York, use of face masks, hand hygiene compliance and strict adherence to contact precautions during Covid-19 pandemic resulted in a decrease in HAIs. [ 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…The hand is therefore the most important route of infection transmission. For this reason, hand hygiene has been emphasized (5)(6)(7)(8).…”
mentioning
confidence: 99%